Cyclosporine-A induced nephrotoxicity is associated with decreased renal bone morphogenetic protein-7 expression in rats - YAVUZ, DİLEK; ARIKAN, İZZET HAKKI; TUĞLULAR, ZÜBEYDE SERHAN (ELSEVIER SCIENCE INC, 2004)
The aim of our study was to investigate bone morphogenetic protein-7 (BMP-7) expression in a rat model of chronic cyclosporine (CsA) toxicity compare with healthy controls, as well as the influence of treatment with the angiotensin-converting enzyme inhibitor (ACEI) quinapril. Twenty-four male Wistar rats were divided into groups of eight animals treated with CsA (15 mg/kg intraperitoneally) for 8 weeks (CsA group) without or with quinapril (10 mg/kg per day in the drinking water: CsA group + Q) for comparison with healthy controls (H group). The renal tissues were examined by light microscopy for CsA toxicity; specifically, tubulointerstitial damage and afferent arteriolopathy as well as BMP-7 expression were serniquantitatively scored by immunohistochemical staining. Mean CsA levels were 1982 ng/mL and 1968 ng/mL for the CsA and CsA + Q groups, respectively. At the end of the study period, the mean serum creatinine levels were 0.8 +/- 0.2 mg/dL, 1.6 +/- 0.8 mg/dL, and 1.4 +/- 0.8 mg/dL for the H, CsA, and CsA + Q groups, respectively. Interstitial fibrosis, tubular atrophy, and afferent arteriolar hyalinization were present in the CsA group and, to a lesser degree, in the CsA + Q group, compared with the H group. CsA-treated rats displayed significantly decreased BMP-7 expression compared with healthy controls (P < .0005). BMP-7 expression was higher among the CsA + Q group than the the group CsA group. In a rat model histologic changes characteristic of CsA-induced nephrotoxicity are associated with decreased expression of BMP-7, which seems to be at least partially restored by ACE inhibition.